YES Problem: f(0()) -> s(0()) f(s(x)) -> g(s(s(x))) g(0()) -> s(0()) g(s(0())) -> s(0()) g(s(s(x))) -> f(x) Proof: DP Processor: DPs: f#(s(x)) -> g#(s(s(x))) g#(s(s(x))) -> f#(x) TRS: f(0()) -> s(0()) f(s(x)) -> g(s(s(x))) g(0()) -> s(0()) g(s(0())) -> s(0()) g(s(s(x))) -> f(x) EDG Processor: DPs: f#(s(x)) -> g#(s(s(x))) g#(s(s(x))) -> f#(x) TRS: f(0()) -> s(0()) f(s(x)) -> g(s(s(x))) g(0()) -> s(0()) g(s(0())) -> s(0()) g(s(s(x))) -> f(x) graph: g#(s(s(x))) -> f#(x) -> f#(s(x)) -> g#(s(s(x))) f#(s(x)) -> g#(s(s(x))) -> g#(s(s(x))) -> f#(x) Matrix Interpretation Processor: dimension: 1 interpretation: [g#](x0) = x0, [f#](x0) = x0 + 1, [g](x0) = 1, [s](x0) = x0 + 1, [f](x0) = 1, [0] = 0 orientation: f#(s(x)) = x + 2 >= x + 2 = g#(s(s(x))) g#(s(s(x))) = x + 2 >= x + 1 = f#(x) f(0()) = 1 >= 1 = s(0()) f(s(x)) = 1 >= 1 = g(s(s(x))) g(0()) = 1 >= 1 = s(0()) g(s(0())) = 1 >= 1 = s(0()) g(s(s(x))) = 1 >= 1 = f(x) problem: DPs: f#(s(x)) -> g#(s(s(x))) TRS: f(0()) -> s(0()) f(s(x)) -> g(s(s(x))) g(0()) -> s(0()) g(s(0())) -> s(0()) g(s(s(x))) -> f(x) Matrix Interpretation Processor: dimension: 1 interpretation: [g#](x0) = 0, [f#](x0) = 1, [g](x0) = 0, [s](x0) = 0, [f](x0) = 0, [0] = 0 orientation: f#(s(x)) = 1 >= 0 = g#(s(s(x))) f(0()) = 0 >= 0 = s(0()) f(s(x)) = 0 >= 0 = g(s(s(x))) g(0()) = 0 >= 0 = s(0()) g(s(0())) = 0 >= 0 = s(0()) g(s(s(x))) = 0 >= 0 = f(x) problem: DPs: TRS: f(0()) -> s(0()) f(s(x)) -> g(s(s(x))) g(0()) -> s(0()) g(s(0())) -> s(0()) g(s(s(x))) -> f(x) Qed